Highly dispersed RuCo clusters on N-doped carbon shell for Li–O2/CO2 batteries and exploitation of the synergistic effect of O2 and CO2. Issue 2 (12th December 2022) - Lian, Yuebin; Xiao, Long; Yang, Xiaoyu; Xu, Weilong; Du, Xiaojiao; Hong, Yilun; Zheng, Min; Peng, Yang
Abstract : The respective roles of O2 and CO2 in Li–O2 /CO2 batteries are investigated and the capacity current rate gas composition relationship is elucidated. Abstract : Li–O2 /CO2 batteries are of central importance for environmentally friendly energy technologies. However, the battery performance still needs to be improved, while the factors affecting the battery capacity are still ambiguous. Herein, we directly synthesized a series of N-doped carbon shell-encapsulated RuCo clusters to improve the battery performance as well as to deeply investigate the catalytic mechanism. Due to the porous structure and evenly dispersed RuCo alloy, the obtained Li–O2 /CO2 battery showed excellent discharge and charge performance as well as a long-time cyclic stability of 550 h and 560 cycles. In addition, the catalytic pathway was verified by comparing the discharge voltage of Li–O2 and Li–O2 /CO2, which confirmed the route of 4Li + + O2 + 2CO2 + 4e − = 2Li2 CO3 . To evaluate the effects of O2 during the discharge process, the catalytic kinetics and battery capacity were verified by monitoring the capacity–current rate–O2 content relationship. In conclusion, the capacity of Li–O2 /CO2 batteries relies on a balance of both the discharge current and O2 -diffusion rate as well as the crystallization process of Li2 CO3 .